Withdrawal of southwest monsoon 1985 -Diagnostic study of cyclonic storms and onset of northeast monsoon (MAUSAM, 1988)
In this paper a study has been made of the four cyclonic disturbances that formed in the first fortnight of October 1985 in the Indian seas. The longitude, where these disturbances recurved, progressively advanced from 75° E to 90° E. This is due to the displacement of a quasi-stationary westerly trough in the upper atmosphere from 70° E to 90° E, which further led to the withdrawal of SW monsoon and onset of NE monsoon. The entire development process and steering of these disturbances took place because of their interaction with the westerly troughs of middle latitude.